Crystal structure diversity in the bis[hydrotris(3,5-dimethylpyrazolyl)borate]iodouranium(III) complex: from neutral to cationic forms - Antunes, Maria Augusta; Santos, Isabel C; Bolvin, Hélène; Pereira, Laura C J; Mazzanti, Marinella; Marçalo, Joaquim; Almeida, Manuel (Dalton transactions : an international journal of inorganic chemistry, 2013)
The iodouranium(III) complex with two hydrotris(3,5-dimethylpyrazolyl)borate ligands is shown to adopt three closely related forms in the solid state. In addition to the previously reported structure for [U(Tp(Me2))2I], in which one of the pyrazolyl rings coordinates side-on to the U atom, another structure incorporating solvent molecules presents undistorted pyrazol rings, and a third one is the ionic compound [U(Tp(Me2))2]I. The implications of this structural diversity for the recently reported single ion magnet behaviour in this complex are discussed, namely on the basis of quantum chemistry calculations. The main effect of the bonding of the iodine atom to uranium is the increase of the size of the first coordination sphere and lowering of the symmetry of the molecule, resulting in a smaller crystal field splitting.